2020
DOI: 10.3847/1538-4357/ab6dc6
|View full text |Cite
|
Sign up to set email alerts
|

The Deepest Radio Observations of Nearby SNe Ia: Constraining Progenitor Types and Optimizing Future Surveys

Abstract: We report deep radio observations of nearby Type Ia supernovae (SNe Ia) with the electronic Multi-Element Radio Linked Interferometer Network and the Australia Telescope Compact Array. No detections were made. With standard assumptions for the energy densities of relativistic electrons going into a power-law energy distribution and the magnetic field strength (ò e =ò B =0.1), we arrive at upper limits on mass-loss rate for the progenitor system of SN2013dy(SN 2016coj, SN 2018gv, SN 2018pv, SN 2019np) of-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 100 publications
3
37
0
Order By: Relevance
“…Wang et al (2019) found that the SNe Ia with high speed Si II features tend to be systematically associated with blueshifted Na I D lines. According to these studies, the distances of the CSM to the SNe range from 10 15 cm to 10 19 cm, and the mass loss rates that lead to such CSM are usually lower than 10 −4 ∼ 10 −9 M /year if they are the results of steady stellar winds, consistent with the constraints set by the X-ray and radio observations (Margutti et al 2014;Pérez-Torres et al 2014;Chomiuk et al 2016;Lundqvist et al 2020).…”
Section: Introductionsupporting
confidence: 59%
“…Wang et al (2019) found that the SNe Ia with high speed Si II features tend to be systematically associated with blueshifted Na I D lines. According to these studies, the distances of the CSM to the SNe range from 10 15 cm to 10 19 cm, and the mass loss rates that lead to such CSM are usually lower than 10 −4 ∼ 10 −9 M /year if they are the results of steady stellar winds, consistent with the constraints set by the X-ray and radio observations (Margutti et al 2014;Pérez-Torres et al 2014;Chomiuk et al 2016;Lundqvist et al 2020).…”
Section: Introductionsupporting
confidence: 59%
“…Our startling results require closer examination. First, the values of B , including the value for average remnant properties, spread over two orders of magnitude for remnant averages, and for Kepler in particular, are far lower than the 0.1 -0.01 often assumed for nonrelativistic shocks (e.g., Lundqvist et al 2020). A more sophisticated model for B (Sarbadhicary et al 2017) predicts values which, while not constant, range only over a factor of 3.…”
Section: Discussionmentioning
confidence: 88%
“…It appears to have been the standard assumption in early GRB modeling, which seems to be where the notation originated (e.g., Sari et al 1998). The notation, and the assumption that these fractions remain constant as the shock wave evolves, have become widespread in modeling radio emission from supernovae and SNRs as well as GRBs (e.g., Lundqvist et al 2020). Typical assumed values for these fractions are in the range 0.01 to 0.1 for GRBs (e.g., Nava et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, we use the "cool," "shallowsilicon," and "core-normal" groups. We also incorporate data compiled in Lundqvist et al (2020) and those presented in Mooley et al (2016) and Ryder et al (2019).…”
Section: The Allowed Fraction Of Sne Ia With Csm Shellsmentioning
confidence: 99%
“…Despite extensive observations of SNe Ia at radio wavelengths, there are no published radio detections of SNe Ia to date, even for those known to be interacting. Upper limits on radio luminosity imply that the CSM around typical SNe Ia is substantially lower density than observed around most core-collapse SNe, assuming the CSM is a continuous medium like a wind (Weiler et al 2002;Pérez-Torres et al 2014;Chomiuk et al 2016;Lundqvist et al 2020).…”
Section: Introductionmentioning
confidence: 97%